Reorientasi Keagamaan dan Konseptualisasi Ukhuwah Islamiyah: Dua Kasus dari Jawa Timur - Turmudi, Endang (P2KK LIPI, 1997)
This article discusses the social relationship between Muslim groups in Jombang and Pasuruan, East Java. It highlights the relationship between traditionalist orthodox Muslim represented by NU and Modernist Orthodox Muslim represented by Muhammadiyah. The relationship is marked by tension and conflict. This conflicts is inevitable, not only because they do difference practice of Islam but also because they have different political orientation. It is argued, however, that this conflict wll not come into disintegrative situation, since at the cultural level muslims have a common integrated system, us the same focabularies and are bound by the same ideology. In addition, it is interesting to note that there are emerging changes in Muslims’ perspective at grassroots level about their relations with other Muslim groups. Such changes constitute their response to the existing and continuous changes in the socio-political realm. The changes have brought them to reformulate their socio-political order, either concerned with the Islamic leadership or with the Islamic ideals that they must pursue in general. What is important in regard to such reformulation (reevaluation) is the concept of Ukhuwwah Islamiyyah (Muslim Brotherhood). The concept has long been interpreted and used inappropriately. The concept is concerned with relations between Muslim groups, which have long been marked by strong primordialism. The re-evaluation of Ukhuwwah Islamiyyah represents a self crilique by Muslims of themselves after they experienced their misconduct in regard to their relationship with each other. It gives rise to mutual understanding between them and juxiaposes one Muslim to another. It is not accidental that intermarriage between Muslims of various groups in present day Jombang and Pasuruan occurs more often thatn that in the past.